BDNF gene polymorphisms and BDNF serum concentration in schizophrenia patients: a pilot study - Boiko, Anastasiia S.; Mednova, Irina A.; Mikhalitskaya, Ekaterina V.; Paderina, Diana Z.; Petkun, Dmitry A.; Kornetova, Elena G.; Bokhan, Nikolay A.; Ivanova, Svetlana A. (Frontiers in Psychiatry, 2025)
ObjectivesThe search for the genetic basis of the leading symptom domains of schizophrenia is of interest. BDNF is a universal neurotrophin that promotes brain development and neuroplasticity. Our aim was to study polymorphisms of the BDNF gene and serum levels of BDNF in schizophrenia and to analyze the concentration of this marker depending on clinical and genetic characteristics.MethodsA clinical and biological examination of 123 patients with paranoid schizophrenia (F20.0, ICD-10) was conducted. The control group consisted of 193 healthy individuals. Genotyping of polymorphisms (rs6265 and rs11030104) was performed by RT-PCR. BDNF concentration was determined using xMAP technology. Statistical data processing was performed in SPSS software.ResultsA lower BDNF concentration was found in schizophrenia patients than in healthy individuals. Clinical characteristics of the disease, such as duration of the disease and leading clinical symptoms do not affect the level of BDNF. The continuous type of course is characterized by a tendency to decrease the BDNF serum concentration compared to the episodic type. The distribution of rs6265 genotypes differed significantly between the groups of schizophrenia patients and healthy individuals. The TT genotype was more common among the patients and had a predisposing effect on schizophrenia. Serum levels of BDNF did not differ between the patients with different genotypes.ConclusionsOur results support a potential value of studied BDNF protein and gene as a neurobiological marker for schizophrenia pathogenesis and clinical characteristics. Further case-control studies on the BDNF gene and peripheral BDNF levels with larger sample sizes and different ethnic groups are needed to better understand the pathogenesis of the schizophrenia.